Nickel-based catalyst for hydrogen production by ammonia decomposition, and preparation method and application thereof
Patent Information
- Application Number
- CN202610747347.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-05-28
AI Technical Summary
Existing ammonia decomposition catalysts suffer from poor stability due to the aggregation of catalytic active components at high temperatures, failing to meet the requirements of ammonia decomposition under high space velocity conditions. Furthermore, the activity of traditional catalysts decreases at high temperatures, making them unsuitable for medium- or large-scale ammonia decomposition units.
Nickel-based catalysts were prepared by pre-dispersion and low-temperature vacuum rapid evaporation, combined with alkali metal promoters and metal oxide supports, to produce nickel particles with an average particle size of 0.5–8.5 nm, thereby increasing the number of active sites and maintaining uniformity. A mixed support was used to stabilize the catalyst structure.
At a space velocity of 30 L/(gcath), the ammonia decomposition efficiency reaches over 99.6%, which improves the catalyst's lifespan and ammonia decomposition activity, meeting the needs of industrial equipment.
Smart Images

Figure CN122273529B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ammonia decomposition technology, specifically to a nickel-based catalyst for ammonia decomposition to produce hydrogen, its preparation method, and its application. Background Technology
[0002] Among numerous renewable energy sources, hydrogen energy, with its green and carbon-free characteristics, is considered a highly promising energy carrier, playing a crucial role in promoting energy structure transformation and addressing climate change. However, the widespread application of hydrogen energy still faces many challenges, among which hydrogen storage and transportation are particularly prominent. Currently, traditional hydrogen storage and transportation methods suffer from numerous shortcomings, including safety hazards, high energy consumption, and complex and costly liquefaction processes. Therefore, exploring new and efficient hydrogen storage and transportation methods is key to the development of hydrogen energy.
[0003] Ammonia, as a potential hydrogen storage and transportation medium, has attracted widespread attention due to its high hydrogen storage capacity (17.8 wt%), liquefaction at room temperature requiring only 8.5 atmospheres, and high volumetric energy density. Furthermore, the synthesis, liquefaction, storage, and transportation technologies for ammonia are well-established, providing strong support for its large-scale application as a hydrogen carrier. Ammonia decomposition hydrogen production technology allows for on-site hydrogen production at locations where hydrogen is needed, offering convenience, speed, and the absence of CO2 throughout the process. x The release of pollutants such as ammonia decomposition makes hydrogen production one of the ideal methods for producing hydrogen in various industrial sectors in the future.
[0004] Existing commercial catalysts are mainly nickel-based, and their catalytic activity is generally low below 700 °C. Furthermore, the low space velocity is insufficient for medium- or large-scale ammonia decomposition units. Simultaneously, since ammonia decomposition is an endothermic reaction requiring high temperatures, the active components of the catalyst are typically affected by high temperatures, i.e., the grain size gradually increases, and the number of active sites decreases, leading to a gradual decrease in ammonia decomposition activity during the high-temperature decomposition process.
[0005] Among existing catalyst technologies, Chinese patent CN117839709A discloses a method for preparing an ammonia decomposition catalyst and its application in the ammonia decomposition reaction, which synthesizes an ammonia decomposition catalyst with cobalt or nickel as the active metal in a one-step sol-gel process. Although it can achieve a decomposition rate of >95% at 600 °C, it uses 6 L / (g) cat h) The airspeed is too low to meet the needs of industrial equipment.
[0006] Chinese patent CN118122321A discloses a method for preparing and applying a microwave-assisted Ru / CeO2 ammonia decomposition catalyst. The catalyst is easy to prepare, has a short preparation cycle, and reduces preparation costs. Although the patent mentions that the catalyst has high thermal stability, the example only underwent 15 hours of stability operation, which is far from meeting the operating conditions of a large-scale ammonia decomposition device.
[0007] Therefore, there is an urgent need in this field to develop an ammonia decomposition catalyst that can adapt to high space velocity conditions. Summary of the Invention
[0008] To address the aforementioned problems, this invention provides a nickel-based catalyst for ammonia decomposition, its preparation method, and its application. The nickel-based catalyst of this invention overcomes the defect in existing technologies where the active components agglomerate after heating, leading to poor stability. This allows for the achievement of high stability at a concentration of 30 L / (g) cat h) Under the reaction conditions of space velocity, the ammonia decomposition efficiency at 600 °C reaches over 99.6%, which is of great significance for the scale-up of catalyst preparation.
[0009] In a first aspect, the present invention provides a nickel-based catalyst for hydrogen production from ammonia decomposition, the catalyst comprising an active component, an auxiliary agent, and an oxide support; The active component is nickel, and the average particle size of the active component is 0.5~8.5 nm. The additive is an alkali metal; The oxide support is an oxide of an element selected from the following group: transition metal elements, rare earth metal elements, alkaline earth metal elements, carbon group metal elements, boron group metal elements, or a combination thereof; The active component accounts for 3-50 wt% of the total mass of the catalyst, the auxiliary agent accounts for 2-12 wt% of the total mass of the catalyst, and the remainder is an oxide support.
[0010] In another preferred embodiment, the active component accounts for 4 to 40 wt% of the total mass of the catalyst, preferably 5 to 35 wt%, more preferably 5 to 30 wt%, and most preferably 12 to 30 wt%.
[0011] In another preferred embodiment, the active component accounts for 15 to 30 wt% of the total mass of the catalyst.
[0012] In another preferred embodiment, the additive accounts for 3 to 12 wt% of the total mass of the catalyst, preferably 3 to 10 wt%, and more preferably 3 to 9 wt%.
[0013] In a preferred embodiment, the catalyst has a specific surface area of 10 to 400 m². 2 / g.
[0014] In another preferred embodiment, the catalyst has a specific surface area of 15 to 380 m². 2 / g, preferably 20 ~ 350 m 2 / g.
[0015] In another preferred embodiment, the catalyst has a specific surface area of 250 to 350 m². 2 / g, the optimal value is 270~340m 2 / g.
[0016] In a preferred embodiment, the average particle size of the active component is 1.0 to 8.5 nm.
[0017] In another preferred embodiment, the average particle size of the active component is 1.0 to 8.0 nm, preferably 1.5 to 7.5 nm, and more preferably 1.5 to 6.5 nm.
[0018] In another preferred embodiment, the average particle size of the active component is 1.5 to 6 nm, preferably 1.5 to 5.5 nm, and more preferably 2.5 to 5.5 nm.
[0019] In a preferred embodiment, the adjuvant is selected from the group consisting of lithium, sodium, potassium, or combinations thereof.
[0020] In a preferred embodiment, the transition metal element is selected from the group consisting of iron, cobalt, titanium, vanadium, chromium, manganese, zirconium, or combinations thereof; The rare earth metal element is selected from the group consisting of lanthanum, cerium, praseodymium, neodymium, or a combination thereof; The alkaline earth metal element is selected from the following group: magnesium, calcium, strontium, barium, or a combination thereof; The carbon group metal elements are selected from the following group: silicon, germanium, or combinations thereof; The boron group metals are selected from the following group: aluminum, gallium, or combinations thereof.
[0021] In another preferred embodiment, the oxide support is an oxide of an element selected from the group consisting of zirconium, magnesium, silicon, aluminum, lanthanum, cerium, titanium, or a combination thereof.
[0022] In another preferred embodiment, the oxide support is selected from the group consisting of aluminum oxide, lanthanum oxide, or combinations thereof.
[0023] In another preferred embodiment, the specific surface area of the oxide support is 10~400 m². 2 / g, preferably 15~380 m 2 / g, preferably 25~360 m 2 / g, the optimal value is 300~350 m 2 / g.
[0024] In another preferred embodiment, the specific surface area of the hybrid carrier is 10~400 m². 2 / g, preferably 15~380 m 2 / g, more preferably 20~350 m 2 / g, the optimal value is 300~350 m 2 / g.
[0025] A second aspect of the present invention provides a method for preparing a nickel-based catalyst for hydrogen production from ammonia decomposition as described in the first aspect of the present invention, the method comprising the following steps: (1) Add one or more of the following to the alkali metal precursor salt solution: transition metal oxide, rare earth metal oxide, alkaline earth metal oxide, carbon group metal oxide, and boron group metal oxide; stir at 40-80 °C for 1-5 h; filter to obtain filter cake; wash and dry the filter cake; calcine at 450-900 °C for 1-10 h under nitrogen or air atmosphere at a heating rate of 2-10 °C / min to obtain powder and mixed carrier. (2) Add the nickel precursor salt to the solvent, stir at 0~50 ℃ for 30~60 min, add the complexing agent, and obtain a pre-dispersion; (3) Add the mixed support obtained in step (1) to the solvent, stir at 20~30 ℃ for 30~60 min, slowly add the pre-dispersion obtained in step (2) to obtain a suspension; remove the solvent from the suspension to obtain the catalyst precursor; (4) The catalyst precursor obtained in step (3) is dried and made into powder. It is first calcined at 350-650 ℃ for 1-10 h at a heating rate of 5-30 ℃ / min under nitrogen or air atmosphere, and then reduced in a reducing atmosphere for 1-10 h to obtain the nickel-based catalyst. The solvent is distilled water, deionized water, or ethanol.
[0026] In another preferred embodiment, step (1) further includes the following steps: adding one or more of the following elements to an alkali metal precursor salt solution: transition metal oxide, rare earth metal oxide, alkaline earth metal oxide, carbon group metal oxide, and boron group metal oxide; stirring at 40-100 °C for 1-4 h; filtering, washing, drying; calcining at 450-900 °C for 1-4 h under nitrogen or air atmosphere; and grinding into fine powder to obtain a mixed carrier.
[0027] In another preferred embodiment, in step (1), the drying includes drying at 100~140 °C for 2~6 h.
[0028] In another preferred embodiment, step (1) further includes the following steps: heating to 450-900 °C at a heating rate of 2-30 °C / min under a nitrogen or air atmosphere, and calcining at the above temperature for 1-4 h.
[0029] In another preferred embodiment, step (2) further includes the following steps: dissolving the nickel precursor salt in deionized water or ethanol, stirring at 10~50 °C for 20~80 min at a stirring rate of 200~700 rpm, adding a complexing agent, and obtaining a pre-dispersion.
[0030] In another preferred embodiment, step (2) further includes the following steps: dissolving the nickel precursor salt in deionized water or ethanol, stirring at 20-35 °C for 20-80 min at a stirring rate of 300-600 rpm, adding a complexing agent, and obtaining a pre-dispersion.
[0031] In another preferred embodiment, step (3) further includes the following steps: adding the mixed carrier from step (1) to deionized water or ethanol, stirring at 20-35 °C for 20-80 min, adding the pre-dispersion liquid from step (2) dropwise, and continuing to stir for 1-4 h to obtain a suspension.
[0032] In another preferred embodiment, step (3) further includes the following step: removing the solvent from the suspension by vacuum low-temperature evaporation to obtain the catalyst precursor.
[0033] In another preferred embodiment, step (4) further includes the following steps: (4a) The precursor of the catalyst is dried and ground into powder; (4b) Under nitrogen or air atmosphere, the powder in step (5a) is heated to 400-900 °C at a heating rate of 2-40 °C / min and calcined for 2-6 h to obtain the sintered product; (4c) The sintered product obtained in step (4b) is reduced in a reducing atmosphere for 1 to 4 h to obtain a nickel-based catalyst.
[0034] In another preferred embodiment, step (4b) includes the following steps: under a nitrogen or air atmosphere, the powder from step (5a) is heated to 400-900 °C at a heating rate of 5-30 °C / min for 2-6 h to obtain a sintered product.
[0035] In a preferred embodiment, in step (1), the alkali metal precursor salt is selected from the group consisting of potassium nitrate, sodium nitrate, potassium carbonate, sodium carbonate, or combinations thereof.
[0036] In another preferred embodiment, in step (1), the alkali metal precursor salt is potassium nitrate.
[0037] In another preferred embodiment, in step (1), the concentration of the alkali metal precursor salt solution is 0.1~5 mol / L, preferably 0.2~4 mol / L, and more preferably 0.2~2 mol / L.
[0038] In another preferred embodiment, in step (2), the nickel precursor salt is selected from the group consisting of nickel acetate, nickel nitrate, nickel acetylacetone, nickel aminosulfonate, or combinations thereof.
[0039] In another preferred embodiment, in step (2), the precursor salt of nickel is nickel nitrate.
[0040] In a preferred embodiment, in step (2), the complexing agent is selected from the group consisting of: o-phenanthroline, polyvinylpyrrolidone, citric acid, ethylenediaminetetraacetic acid, or combinations thereof.
[0041] In another preferred embodiment, in step (2), the complexing agent is o-phenanthroline.
[0042] In another preferred embodiment, in step (2), the mass ratio of the nickel precursor salt to the complexing agent is 1: (1.0~10.0), preferably 1: (1.0~8.0), more preferably 1: (1.0~4.0), and most preferably 1: (1.0~3.0).
[0043] In another preferred embodiment, in step (2), the volume of the deionized water or ethanol is 40-60 mL.
[0044] In a preferred embodiment, in step (4), the reducing atmosphere is composed of an inorganic gas and Ar; wherein the inorganic gas is selected from the group consisting of NH3, H2, or a combination thereof.
[0045] In another preferred embodiment, in step (5), the inorganic gas accounts for 5 to 20 v / v% of the total volume of the reducing atmosphere, preferably 8 to 20 v / v%, more preferably 8 to 14 v / v.
[0046] In another preferred embodiment, in step (4), the inorganic gas is H2.
[0047] A third aspect of the present invention provides the application of a nickel-based catalyst as described in the first aspect of the present invention in the ammonia decomposition to hydrogen production reaction, wherein the nickel-based catalyst is used at an ammonia gas flow rate of 10~30 L / (g). cat The ammonia decomposition to produce hydrogen reaction is carried out under the conditions of h).
[0048] In another preferred embodiment, the hydrogen production rate of the ammonia decomposition hydrogen production reaction at 600 °C is 30~35 mmol / (g). cat min).
[0049] In another preferred embodiment, the application includes: placing a nickel-based catalyst in an ammonia atmosphere at 20-30°C for 1-4 hours before the ammonia decomposition to hydrogen production reaction, and then raising the temperature to 350-650°C at an ammonia flow rate of 10-30 L / (g). cat The ammonia decomposition to produce hydrogen reaction is carried out under the conditions of h).
[0050] In another preferred embodiment, the application includes: before the ammonia decomposition to hydrogen production reaction, placing a nickel-based catalyst at 20-30°C and introducing ammonia gas at a flow rate of 1-5 L / h for 1-4 h, subsequently raising the temperature to 350-650°C and introducing ammonia gas at a flow rate of 10-30 L / (g) cat The ammonia decomposition to produce hydrogen reaction is carried out under the conditions of h).
[0051] Compared with existing technologies, the beneficial effects of this invention are: 1. In the preparation process of the supported nickel-based catalyst provided by the present invention, the dispersion of the active component metallic nickel is improved by pre-dispersion and low-temperature vacuum rapid evaporation, the particle size of nickel is reduced, the number of surface active sites is increased, and the ammonia decomposition activity is greatly enhanced.
[0052] 2. The preparation method of the present invention uses a complexing agent to pre-disperse the active component metallic nickel, so that it maintains good uniformity after calcination and reduction, and has a reasonable size (the average particle size of elemental nickel is 0.5~8.5 nm, preferably 2.9~4.1 nm), which greatly alleviates the agglomeration of the active component nickel during the heating process and improves the service life of the catalyst.
[0053] 3. The metal oxides used in the mixed support of this invention have a stable structure and are difficult to react with reducing gases such as NH3 and H2, thereby effectively improving the catalyst lifetime.
[0054] 4. The present invention prepares a mixed support by co-calcining alkali metal additives and metal oxides, which further optimizes the support for nickel loading. The mixed support of the present invention is beneficial to the uniform distribution of metallic nickel particles. Attached Figure Description
[0055] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0056] Figure 1These are X-ray powder diffraction patterns of the catalysts used in Examples 1-4 and Comparative Examples 1-2 before their use.
[0057] Figure 2 This is the X-ray powder diffraction pattern of the catalyst after use in Example 2.
[0058] Figure 3 This is a transmission electron microscope image of the catalyst in Example 2 before its use.
[0059] Figure 4 This is a statistical diagram of the crystal size distribution of the catalyst before use in Example 2. Detailed Implementation
[0060] Preparation method of nickel-based catalyst of the present invention This invention provides a method for preparing a highly active nickel-based catalyst for hydrogen production from ammonia decomposition, comprising the following technical solutions: (1) Select one or more of transition metal element oxides, rare earth metal element oxides, alkaline earth metal element oxides, carbon group metal element oxides, and boron group metal element oxides, add them to the alkali metal precursor salt solution, stir for 2-3 h in a water bath or oil bath at 40-80 ℃, filter to obtain filter cake, wash and dry the filter cake and place it in a tube furnace, calcine at 450-900 ℃ in a nitrogen or air atmosphere, with a heating rate of 2-10 ℃ / min and a calcination time of 2-4 h, grind the calcined coarse particles into fine powder to obtain the treated oxide carrier (i.e., mixed carrier). (2) Dissolve the nickel metal precursor salt in distilled water, deionized water or ethanol, stir at 0~50 ℃ for 30~60 min at a stirring rate of 200~500 rpm, and add a complexing agent to prepare a pre-dispersion. (3) Add the treated oxide support from step (1) to distilled water, deionized water or ethanol, stir at 20~30℃ for 30~60 min, then add the pre-dispersion liquid from step (2) dropwise, and continue stirring for 1~2 h to obtain a suspension; remove the solvent from the obtained suspension by vacuum low-temperature evaporation to obtain the catalyst precursor; (4) The precursor obtained in step (3) is dried and ground into powder; the powder is heated to 350-650 ℃ for 2-6 h at a heating rate of 5-30 ℃ / min under nitrogen or air atmosphere to obtain sintered product; the sintered product is activated in a reducing atmosphere (NH3 and / or H2) / Ar for 1-10 h to obtain nickel-based catalyst.
[0061] Furthermore, in the above technical solution, the catalyst includes an active component, an auxiliary agent, and a treated oxide support, and the specific surface area of the catalyst is 20.6~330.5 m².2 / g; The active component is elemental nickel, and the average particle size of the active component is 0.5~5.5 nm, preferably 2.9~4.1 nm; The content of elemental nickel is 5.0% to 30.0% by mass percentage, the content of additives is 5.0% to 10.0%, and the balance is oxide carrier.
[0062] Furthermore, in the above technical solution, the transition metal element oxide, rare earth metal element oxide, alkaline earth metal element oxide, carbon group metal element oxide, and boron group metal element oxide are one of zirconium, magnesium, silicon, aluminum, lanthanum, cerium, or titanium oxide.
[0063] Preferably, the oxide is either aluminum oxide or lanthanum oxide.
[0064] Furthermore, in the above technical solution, the specific surface area of the oxide support is 26.7~360.4 m². 2 / g.
[0065] Furthermore, in the above technical solution, the alkali metal precursor salt of the auxiliary agent is one of potassium nitrate, sodium nitrate, potassium carbonate, or sodium carbonate, preferably potassium nitrate.
[0066] Furthermore, in the above technical solution, the concentration of the alkali metal precursor salt solution of the auxiliary agent is 0.1~2 mol / L, preferably 0.99 mol / L.
[0067] Furthermore, in the above technical solution, the specific surface area of the treated oxide support is 23.2~343.7 m². 2 / g, preferably 299.8~343.7 m 2 / g.
[0068] Furthermore, in the above technical solution, the nickel metal precursor salt is one of nickel acetate, nickel nitrate, nickel acetylacetonate, and nickel aminosulfonate, preferably nickel nitrate.
[0069] Furthermore, in the above technical solution, the complexing agent is one or more of o-phenanthroline, polyvinylpyrrolidone, citric acid, and ethylenediaminetetraacetic acid; The mass ratio of the nickel salt to the complexing agent is 1:1.0 to 3.0, and can be one of 1:1.0, 1:1.2, 1:1.5, 1:1.8, 1:2.0, 1:2.2, 1:2.5 or 1:3.0, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0070] Preferably, the complexing agent is o-phenanthroline; the molar ratio of the nickel salt to the complexing agent is 1:2.0~3.0.
[0071] Furthermore, in the above technical solution, the solvent, deionized water or ethanol, is 40-60 mL.
[0072] Preferably, the solvent is ethanol.
[0073] Furthermore, in the above technical solution, the reducing atmosphere is a mixture of at least one of NH3 and H2 with Ar, wherein the volume fraction of NH3 or H2 in the mixture is 5-20%.
[0074] Preferably, the reducing atmosphere is H2 with a volume fraction of 10%.
[0075] Application of the nickel-based catalyst of this invention This invention synthesizes a nickel-based ammonia decomposition catalyst by a low-temperature rapid solvent evaporation method, which is suitable for ammonia decomposition to produce hydrogen using pure ammonia as raw material.
[0076] The nickel-based catalyst of this invention is used in the ammonia decomposition hydrogen production process: Before the ammonia decomposition hydrogen production reaction begins, the nickel-based catalyst is first pre-adsorbed in the reactor (i.e., the nickel-based catalyst is placed at room temperature (20~30 °C) and ammonia gas is introduced at a flow rate of 1~5 L / h for 1~4 h), then the reaction temperature is raised to 350~650 °C, and then ammonia gas is introduced at a flow rate of 10~30 L / (g) cat Under certain conditions (h), ammonia decomposition is promoted, and at 600 °C, the rate of hydrogen production from this decomposition reaction can reach 30~35 mmol / (g). cat min).
[0077] Example 1 (1) 3.005 g of alumina was added to 100 mL of 10 w / v% (0.99 mol / L) potassium nitrate solution and stirred at 60 °C for 2 h. The filter cake was then obtained by filtration, washed with deionized water, and dried at 120 °C for 4 h. The dried material was then placed in an air atmosphere and heated to 500 °C at a heating rate of 5 °C / min, and calcined at 500 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain alumina mixed carrier (about 3.543 g).
[0078] (2) Dissolve 1.655 g of nickel nitrate in 40 mL of solvent ethanol and stir at 400 rpm for 30 min at 25 °C; then add 3.684 g of o-phenanthroline to prepare a pre-dispersion.
[0079] (3) Take 2 g of the alumina mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 25 °C for 30 min. Then add the pre-dispersion liquid prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0080] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 450 °C at a heating rate of 5 °C / min in an air atmosphere and calcined at 450 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.334 g of Ni / Al2O3 catalyst, wherein the active component is nickel with a content of about 15.2 wt%, potassium with a content of about 6.9 wt%, and the remainder is alumina.
[0081] Example 2 2.578 g of Ni / Al2O3 catalyst was prepared according to the preparation method in Example 1. Based on the total mass of the catalyst being 100.0 wt%, the loading of active component metallic nickel was about 20.4 wt%, the content of auxiliary agent potassium was about 6.0 wt%, and the balance was alumina support.
[0082] The preparation method of this embodiment is the same as that of Example 1, except that the mass of nickel nitrate, the precursor salt of the active component nickel, is 2.207 g, and the mass of o-phenanthroline, the complexing agent, is 5.297 g.
[0083] Example 3 2.852 g of Ni / Al2O3 catalyst was prepared according to the preparation method in Example 1. Based on the total mass of the catalyst being 100.0 wt%, the loading of active component metallic nickel was about 30.0 wt%, the content of auxiliary agent potassium was about 6.6 wt%, and the balance was alumina support.
[0084] The preparation method of this embodiment is the same as that of Example 1, except that the mass of nickel nitrate precursor salt of active component nickel is 3.311 g and the complexing agent is 5.959 g of polyvinylpyrrolidone.
[0085] Example 4 2.608 g of Ni / Al2O3 catalyst was prepared according to the preparation method in Example 1. Based on the total mass of the catalyst being 100.0 wt%, the loading of active component metallic nickel was about 25.7 wt%, the content of auxiliary agent potassium was about 6.4 wt%, and the balance was alumina support.
[0086] The preparation method of this embodiment is the same as that of Example 1, except that the mass of nickel nitrate precursor salt of active component nickel is 2.759 g, the complexing agent is 5.518 g of ethylenediaminetetraacetic acid, and the solvent used in steps (2) and (3) is deionized water.
[0087] Example 5 (1) 3.001 g of zirconium oxide was added to 100 mL of 5 w / v% (0.38 mol / L) potassium carbonate solution and stirred at 60 °C for 2 h. The filter cake was then obtained by filtration, washed with deionized water, and dried at 120 °C for 4 h. The dried material was then placed in an air atmosphere and heated to 450 °C at a heating rate of 10 °C / min, and calcined at 450 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain zirconium oxide mixed support (about 3.197 g).
[0088] (2) Dissolve 0.935 g of nickel acetate in 40 mL of solvent ethanol and stir at 30 °C at a stirring speed of 500 rpm for 30 min; then add 2.173 g of citric acid to prepare a pre-dispersion.
[0089] (3) Take 2 g of the zirconium oxide mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 30 °C for 60 min, then add the pre-dispersion liquid prepared in step (2) dropwise, and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0090] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 650 °C at a heating rate of 30 °C / min in an air atmosphere and calcined at 650 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.264 g of Ni / ZrO2 catalyst, wherein the active component is nickel with a content of about 10.3 wt%, potassium with a content of about 4.3 wt%, and the remainder is zirconium oxide.
[0091] Example 6 (1) 3.002 g of magnesium oxide was added to 100 mL of 10 w / v% (1.06 mol / L) sodium carbonate solution and stirred at 80 °C for 2 h. The filter cake was then obtained by filtration, washed with deionized water, and dried at 120 °C for 4 h. The dried material was then placed in an air atmosphere and heated to 900 °C at a heating rate of 20 °C / min, and calcined at 900 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain magnesium oxide mixed carrier (about 3.525 g).
[0092] (2) Dissolve 1.655 g of nickel nitrate in 40 mL of solvent ethanol and stir at 500 rpm for 30 min at 25 °C; then add 3.684 g of o-phenanthroline to prepare a pre-dispersion.
[0093] (3) Take 2.005 g of the magnesium oxide mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 25 °C for 60 min. Then add the pre-dispersion liquid prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0094] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 550 °C at a heating rate of 10 °C / min in an air atmosphere and calcined at 550 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.407 g of Ni / MgO catalyst, wherein the active component is nickel with a content of about 14.9 wt%, sodium with a content of about 6.3 wt%, and the remainder is magnesium oxide.
[0095] Example 7 (1) 3.001 g of silicon dioxide was added to 100 mL of 8 w / v% (0.70 mol / L) potassium carbonate solution and stirred at 80 °C for 2 h. The filter cake was then obtained by filtration, washed with deionized water, and dried at 120 °C for 4 h. The dried material was then placed in an air atmosphere and heated to 650 °C at a heating rate of 10 °C / min, and calcined at 650 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain silicon dioxide mixed carrier (about 3.331 g).
[0096] (2) Dissolve 1.104 g of nickel nitrate in 40 mL of solvent ethanol and stir at 400 rpm for 60 min at room temperature (about 20~30 ℃); then add 3.684 g of o-phenanthroline to prepare a pre-dispersion.
[0097] (3) Take 2.002 g of the silica mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 30 °C for 60 min. Then add the pre-dispersion liquid prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0098] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 900 °C at a heating rate of 20 °C / min in an air atmosphere and calcined at 900 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.232 g of Ni / SiO2 catalyst, wherein the active component is nickel with a content of about 10.1 wt%, potassium with a content of about 6.2 wt%, and the remainder is silicon oxide.
[0099] Example 8 (1) 3.004 g of lanthanum oxide was added to 100 mL of 5 w / v% (0.495 mol / L) potassium nitrate solution and stirred at 60 °C for 2 h; then the mixture was washed three times and dried at 120 °C for 4 h; then the dried material was placed in an air atmosphere and heated to 900 °C at a heating rate of 25 °C / min, and calcined at 600 °C for 2 h; the calcined coarse particles were ground into fine powder to obtain lanthanum oxide mixed support (about 3.201 g).
[0100] (2) Dissolve 3.310 g of nickel nitrate in 40 mL of solvent ethanol and stir at 30 °C at 400 rpm for 30 min; then add 3.684 g of o-phenanthroline to prepare a pre-dispersion.
[0101] (3) Take 2.004 g of the lanthanum oxide mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 30 °C for 30 min. Then add the pre-dispersion liquid prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0102] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 600 °C at a heating rate of 10 °C / min in an air atmosphere and calcined at 600 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.834 g of Ni / La2O3 catalyst, in which the active component metallic nickel content is about 29.9 wt%, potassium content is about 3.8 wt%, and the remainder is lanthanum oxide.
[0103] Example 9 (1) 3.005 g of cerium oxide was added to 100 mL of 10 w / v % (0.99 mol / L) potassium nitrate solution and stirred at 60 °C for 2 h. The filter cake was then obtained by filtration, washed with deionized water, and dried at 120 °C for 4 h. The dried material was then placed in a nitrogen atmosphere and heated to 600 °C at a heating rate of 10 °C / min, and calcined at 600 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain a cerium oxide mixed support (about 3.531 g).
[0104] (2) Dissolve 0.552 g of nickel nitrate in 40 mL of solvent ethanol and stir at 400 rpm for 60 min at 25 °C; then add 3.6837 g of o-phenanthroline to prepare a pre-dispersion.
[0105] (3) Take 2.002 g of the cerium oxide mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 25 °C for 30 min. Then add the pre-dispersion liquid prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0106] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 900 °C at a heating rate of 25 °C / min in an air atmosphere and calcined at 900 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.115 g of Ni / CeO2 catalyst, wherein the active component is nickel with a content of about 5.2 wt%, potassium with a content of about 8.2 wt%, and the remainder is cerium oxide.
[0107] Comparative Example 1 (without complexing agent) (1) 3.004 g of alumina was added to 100 mL of 10% potassium nitrate solution and stirred in an oil bath at 60 °C for 2 h. The filter cake was then obtained by filtration, washed with distilled water, and dried at 120 °C for 4 h. The dried material was then placed in an air atmosphere and heated to 600 °C at a heating rate of 10 °C / min, and calcined at 600 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain alumina mixed carrier (about 3.360 g).
[0108] (2) Dissolve 2.207 g of nickel nitrate in 40 mL of solvent ethanol and stir at 500 rpm for 30 min at 25 °C to obtain a nickel nitrate solution (without adding complexing agent).
[0109] (3) Take 2.003 g of the alumina mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 25 °C for 30 min. Then add the nickel nitrate solution prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0110] (4) The precursor obtained in step (3) is dried and then ground into powder. Then, it is heated to 600 °C at a heating rate of 10 °C / min in an air atmosphere and calcined at 600 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.365 g of Ni / Al2O3 catalyst, wherein the active component is nickel with a content of about 20.2 wt%, potassium with a content of about 7.2 wt%, and the remainder is alumina.
[0111] Comparative Example 2 (Oxide support without additives) (1) Dissolve 2.759 g of nickel nitrate in 40 mL of solvent ethanol and stir at 400 rpm for 30 min at 25 °C; then add 3.684 g of o-phenanthroline to prepare a pre-dispersion.
[0112] (2) Weigh 2.004 g of untreated alumina support and dissolve it in 60 mL of solvent ethanol. Stir at 25 °C for 30 min. Then add the pre-dispersion liquid prepared in step (1) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0113] (3) The precursor obtained in step (2) is dried and then ground into powder. Then, under a nitrogen atmosphere, the temperature is increased to 600 ℃ at a heating rate of 10 ℃ / min and calcined at 600 ℃ for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.496 g of Ni / Al2O3 catalyst, in which the active component metallic nickel content is about 25.6 wt% and the remainder is alumina.
[0114] Comparative Example 3 (using nickel acetylacetone as the nickel source + oxide support without the addition of additives) (1) Dissolve 2.438 g of nickel acetylacetone in 40 mL of solvent ethanol and stir at 400 rpm for 30 min at 25 °C; then add 3.684 g of o-phenanthroline to prepare a pre-dispersion.
[0115] (2) Weigh 2.004 g of untreated alumina support and dissolve it in 60 mL of solvent ethanol. Stir at 25 °C for 30 min. Then add the pre-dispersion liquid prepared in step (1) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0116] (3) The precursor obtained in step (2) is dried and then ground into powder. Then, it is heated to 550 °C at a heating rate of 5 °C / min in an air atmosphere and calcined at 550 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.530 g of Ni / Al2O3 catalyst, in which the active component metallic nickel content is about 25.1 wt% and the remainder is alumina.
[0117] Comparative Example 4 (No complexing agent + using nickel acetylacetone as the nickel source + oxide carrier without the addition of additives) (1) Dissolve 2.438 g of nickel acetylacetonate in 40 mL of solvent ethanol and stir at 30 °C at 500 rpm for 30 min to obtain nickel acetylacetonate solution (without adding complexing agent).
[0118] (2) Weigh 2.005 g of untreated cerium oxide support and dissolve it in 60 mL of solvent ethanol. Stir at 30 °C for 30 min. Then add the nickel acetylacetone solution prepared in step (1) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0119] (3) The precursor obtained in step (2) is dried and then ground into powder. Then, under a nitrogen atmosphere, the temperature is increased to 650 °C at a heating rate of 10 °C / min and calcined at 650 °C for 4 h to obtain a sintered product. The sintered product is then reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.564 g of Ni / CeO2 catalyst, in which the active component metallic nickel content is about 25.2 wt% and the remainder is cerium oxide.
[0120] Comparative Example 5 (No complexing agent + oxide support without additive treatment + catalyst precursor without calcination) (1) Dissolve 2.759 g of nickel nitrate in 40 mL of ethanol and stir at 30 °C at 500 rpm for 30 min to obtain a nickel nitrate solution (without adding complexing agent).
[0121] (2) Weigh 2.004 g of untreated lanthanum oxide support and dissolve it in 60 mL of solvent ethanol. Stir at 30 °C for 30 min. Then add the nickel nitrate solution prepared in step (1) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to a flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0122] (3) The precursor obtained in step (2) is dried and then ground into powder. The powder is then directly reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.534 g of Ni / La2O3 catalyst, in which the active component metallic nickel content is about 25.0 wt% and the remainder is lanthanum oxide.
[0123] Comparative Example 6 (No complexing agent + catalyst precursor without calcination) (1) 3.003 g of magnesium oxide was added to 100 mL of 8% potassium nitrate solution and stirred at 80 °C for 2 h. The filter cake was then filtered, washed with distilled water, and dried at 120 °C for 4 h. The dried material was then placed in an air atmosphere and heated to 700 °C at a heating rate of 15 °C / min. The material was then calcined at 700 °C for 2 h. The calcined coarse particles were ground into fine powder to obtain magnesium oxide mixed carrier (about 3.322 g).
[0124] (2) Dissolve 2.207 g of nickel nitrate in 40 mL of solvent ethanol and stir at 30 °C at 500 rpm for 30 min to obtain a nickel nitrate solution (without adding complexing agent).
[0125] (3) Take 2.005 g of the magnesium oxide mixed support obtained in step (1) and dissolve it in 60 mL of solvent ethanol. Stir at 30 °C for 60 min. Then add the nickel nitrate solution prepared in step (2) dropwise and continue stirring for 2 h to obtain a suspension. Then transfer the suspension to an eggplant flask and remove the solvent ethanol by low temperature vacuum rapid evaporation to obtain the catalyst precursor.
[0126] (4) The precursor obtained in step (3) is dried and then ground into powder. It is then directly reduced in a 10% H2 / Ar atmosphere for 2 h to obtain 2.121 g Ni / MgO catalyst, in which the active component metallic nickel content is about 19.9 wt%, potassium content is about 5.5 wt%, and the remainder is magnesium oxide.
[0127] Comparative Example 7 The comparative example used a commercial Raney nickel catalyst, which is a nickel-based catalyst (Ni / Al2O3) supported on alumina, with a nickel loading of 15.8 wt%.
[0128] Test Example 1. Specific Surface Area of the Catalyst This test example measured the specific surface area of the oxide support before and after treatment with additives, as well as the specific surface area of the catalyst obtained after loading nickel. The results are shown in Table 1.
[0129] Table 1. Specific surface area of the examples and comparative examples The results above show that neither the addition of additives nor the loading of active components affects the specific surface area of the carrier, indicating that the preparation method of the present invention does not change the carrier structure and helps to maintain the stability of the carrier structure.
[0130] Test Example 2. X-ray powder diffraction pattern, physical properties, and activity evaluation of the catalyst. The catalysts in the embodiments and comparative examples of the present invention were tested under the same conditions.
[0131] Catalyst pretreatment: The catalysts of each example and comparative example were pressed into particles (0.1 g) with a particle size of 0.6~1.2 mm and packed into a quartz tube in a fixed bed; Activity testing conditions: The feed gas was high-purity ammonia (purity > 99.999%), and the mass hourly space velocity (WHSV) of the feed gas was 30 L / (g). cat First, a quartz tube filled with 0.1 g of catalyst was pre-adsorbed for 2 h in an ammonia atmosphere at room temperature of 3 L / h (ammonia flow rate). Then, the fixed bed temperature was increased to 500 ℃, 550 ℃, or 600 ℃, and the ammonia flow rate was 30 L / (g). cat The ammonia decomposition reaction to produce hydrogen was carried out under the conditions of h). A Fuli F70 gas chromatograph was used to collect and analyze the tail gas, with a thermal conductivity detector. The main analyses focused on the concentrations of NH3 and H2 in the tail gas. The initial ammonia concentration and the ammonia concentration at each temperature were recorded, and the concentration results were substituted into the following formula to calculate the ammonia decomposition rate. The results are shown in Table 3.
[0132] The activity of the catalyst is expressed as the NH3 decomposition rate. The higher the activity of the catalyst, the higher the ammonia decomposition rate, where the ammonia decomposition rate = (initial ammonia concentration - ammonia concentration after reaction) / initial ammonia concentration × 100%.
[0133] The X-ray powder diffraction patterns of the catalysts in Examples 1-4 and Comparative Examples 1-2 before use are shown below. Figure 1 As shown, the X-ray powder diffraction pattern of the catalyst after use in Example 2 is as follows. Figure 2 As shown.
[0134] Depend on Figure 1 and Figure 2 It can be seen that no Al2O3 crystalline phase appeared in the catalyst of the present invention before or after use, and it remained an amorphous Al2O3 structure. Furthermore, the Ni grain size only increased slightly after use, indicating that the catalyst structure of the present invention is relatively stable.
[0135] The physical properties of the catalysts in the examples and comparative examples before use are shown in Table 2. The transmission electron microscopy (TEM) images and grain sizes of the catalyst in Example 2 before use are shown in Table 2. Figure 3 and Figure 4 As shown.
[0136] The nickel grain sizes in Table 2 are derived from the grain size statistics of transmission electron microscopy images.
[0137] The activity evaluation results of the catalysts in the examples and comparative examples are shown in Table 3.
[0138] Table 2. Physical property parameters of the examples and comparative examples Table 3. Activity evaluation results of the examples and comparative examples (mass volume hourly space velocity of 30 L / (g)). cat h)) Examples 1-4 are Ni / Al2O3 catalysts prepared using different complexing agents, while Comparative Example 1 is a Ni / Al2O3 catalyst prepared without the addition of any complexing agent.
[0139] As shown in Tables 2 and 3, compared with the catalyst in Comparative Example 1, the active nickel crystal size of Examples 1-4 differs significantly, with the nickel crystal size in Comparative Example 1 being approximately four times that of Examples 1-4. Furthermore, the ammonia decomposition efficiency also differs considerably. At 500 °C, the ammonia decomposition efficiency of Examples 1-4 is approximately three times that of Comparative Example 1. At 600 °C, the ammonia decomposition efficiency of Comparative Example 1 is improved compared to 500 °C, but still only reaches 59.8%, while the ammonia decomposition efficiency of Examples 1-4 can reach as high as 99.9%, and the hydrogen production rate of this reaction at 600 °C is as high as 30-35 mmol / (g). cat min).
[0140] As can be seen from the above, adding a complexing agent helps to reduce the grain size of the active component, metallic nickel, and improves the ammonia decomposition effect (i.e., catalytic activity) of the catalyst. Therefore, the complexing agent is a key reagent in the preparation of the catalyst of this invention.
[0141] Comparative Example 2 is a Ni / Al2O3 catalyst prepared without any additives added to the support; Comparative Example 3 is a Ni / Al2O3 catalyst prepared using nickel acetylacetone as the nickel source without adding any additives to the support; Comparative Example 4 is a Ni / CeO2 catalyst prepared using nickel acetylacetone as the nickel source, without the addition of a complexing agent or any additives to the support; Comparative Example 5 is a Ni / La2O3 catalyst prepared without adding complexing agents, without adding promoters to the support, and without calcining the catalyst precursor; Comparative Example 6 is a Ni / MgO catalyst prepared without the addition of a complexing agent and without calcination of the catalyst precursor; As can be seen from Tables 2 and 3, compared with Examples 1-9, the grain size of metallic nickel in Comparative Examples 2-6 is significantly increased, and the ammonia decomposition efficiency is significantly reduced.
[0142] Therefore, it can be seen that not using nickel acetylacetone as a nickel source, adding complexing agents, adding promoters to the support, and calcining the catalyst precursor all help to reduce the grain size of the active component, metallic nickel, and improve the ammonia decomposition effect (i.e., catalytic activity) of the catalyst.
[0143] Comparative Example 7 is a commercial nickel-based catalyst. As can be seen from Tables 2 and 3, compared with Examples 1 to 9, the grain size of metallic nickel in Comparative Example 7 is significantly larger and the ammonia decomposition efficiency is significantly lower, indicating that the nickel-based catalyst of the present invention has superior ammonia decomposition effect.
[0144] This invention employs a vacuum low-temperature rapid evaporation method to prepare a highly active nickel-based catalyst for ammonia decomposition to hydrogen production. Specifically, this invention uses a complexing agent to pre-disperse active metallic nickel, and then loads the pre-dispersed active metallic nickel onto a mixed support containing an additive and oxides of zirconium, magnesium, silicon, aluminum, lanthanum, or cerium. This maintains a high degree of dispersion of the active metallic nickel, effectively adjusts the particle size of the active metallic nickel, and promotes its uniform dispersion. Simultaneously, the synergistic effect of nickel and the mixed support generates more active sites, thereby accelerating electron transfer during the reaction process and optimizing the chemical environment of nickel. This allows the nickel-based catalyst to operate within a suitable loading range (5–30 wt%) and at a relatively high space velocity (30 L / (g)). cat The ammonia decomposition reaction can still maintain a high conversion rate at both h)) and 600 ℃.
[0145] In summary, the highly active nickel-based catalyst for ammonia decomposition to hydrogen production prepared by the method of this invention can adapt to ammonia decomposition under high space velocity conditions, and its catalytic activity is greatly improved.
[0146] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.
[0147] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nickel-based catalyst for hydrogen production from ammonia decomposition, characterized in that, The catalyst is composed of an active component, an auxiliary agent, and an oxide support, and is prepared using the following steps: (1) Add one or more of the oxide supports to the alkali metal precursor salt solution, stir at 40~80 ℃ for 1~5 h, filter, and obtain filter cake; The filter cake is washed, dried, and calcined at 450-900 °C for 1-10 h under nitrogen or air atmosphere at a heating rate of 2-10 °C / min to obtain a powder and a mixed carrier. (2) Add the nickel precursor salt to the solvent, stir at 0~50 ℃ for 30~60 min, add the complexing agent, and obtain a pre-dispersion; (3) Add the mixed support obtained in step (1) to the solvent, stir at 20~30 ℃ for 30~60 min, slowly add the pre-dispersion obtained in step (2) to obtain a suspension; remove the solvent from the suspension to obtain the catalyst precursor; (4) The catalyst precursor obtained in step (3) is dried and made into powder. It is first calcined at 350-650 ℃ for 1-10 h at a heating rate of 5-30 ℃ / min under nitrogen or air atmosphere, and then reduced in a reducing atmosphere for 1-10 h to obtain the nickel-based catalyst. The solvent is distilled water, deionized water, or ethanol. The active component is nickel, and the average particle size of the active component is 0.5~8.5 nm. The additive is an alkali metal; the alkali metal is selected from the group consisting of lithium, sodium, potassium, or a combination thereof. The oxide support is an oxide of an element selected from the group consisting of zirconium, magnesium, silicon, aluminum, lanthanum, cerium, titanium, or a combination thereof; The complexing agent is selected from the group consisting of o-phenanthroline, ethylenediaminetetraacetic acid, citric acid, or combinations thereof; The active component accounts for 3-50 wt% of the total mass of the catalyst, the auxiliary agent accounts for 2-12 wt% of the total mass of the catalyst, and the remainder is an oxide support.
2. The catalyst according to claim 1, characterized in that, The catalyst has a specific surface area of 10~400 m². 2 / g.
3. The catalyst according to claim 1, characterized in that, The average particle size of the active component is 1.0~8.5 nm.
4. The catalyst according to claim 1, characterized in that, The active component accounts for 5-35 wt% of the total mass of the catalyst.
5. The catalyst according to claim 1, characterized in that, The oxide support is selected from the group consisting of aluminum oxide, lanthanum oxide, or combinations thereof.
6. The catalyst according to claim 1, characterized in that, In step (1), the drying includes drying at 100~140℃ for 2~6 h.
7. The catalyst according to claim 1, characterized in that, In step (1), the alkali metal precursor salt is selected from the group consisting of potassium nitrate, sodium nitrate, potassium carbonate, sodium carbonate, or a combination thereof.
8. The catalyst according to claim 1, characterized in that, In step (2), the nickel precursor salt is selected from the group consisting of nickel acetate, nickel nitrate, nickel acetylacetone, nickel aminosulfonate, or combinations thereof.
9. The catalyst according to claim 1, characterized in that, The mass ratio of the nickel precursor salt to the complexing agent is 1:(1.0~10.0).
10. The catalyst according to claim 1, characterized in that, In step (4), the reducing atmosphere is composed of inorganic gas and Ar; wherein the inorganic gas is selected from the group consisting of NH3, H2, or a combination thereof.
11. The application of the nickel-based catalyst as described in claim 1 in the ammonia decomposition to hydrogen production reaction, characterized in that, The nickel-based catalyst was used at an ammonia flow rate of 10~30 L / (g) cat The ammonia decomposition to produce hydrogen reaction is carried out under the conditions of h).
Citation Information
Patent Citations
Ammonia decomposition catalyst and preparation method and application thereof
CN117839709A
Preparation method and application of microwave-assisted Ru / CeO2 ammonia decomposition catalyst
CN118122321A
Nickel-based ammonia decomposition catalyst and preparation method and application thereof
CN120189949A
